2018
DOI: 10.1038/s41598-018-29884-8
|View full text |Cite
|
Sign up to set email alerts
|

FliS/flagellin/FliW heterotrimer couples type III secretion and flagellin homeostasis

Abstract: Flagellin is amongst the most abundant proteins in flagellated bacterial species and constitutes the major building block of the flagellar filament. The proteins FliW and FliS serve in the post-transcriptional control of flagellin and guide the protein to the flagellar type III secretion system (fT3SS), respectively. Here, we present the high-resolution structure of FliS/flagellin heterodimer and show that FliS and FliW bind to opposing interfaces located at the N- and C-termini of flagellin. The FliS/flagelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Helices α1 and α2 were oriented in a half-opened hairpin structure and interacted with helices α3 and α4 of FliS. Helix 3 was embedded in the flagellar binding pocket, which was consistent with other FliS-FliC structural models (Evdokimov et al, 2003;Altegoer et al, 2018;Xing et al, 2018). Helix 4 was located near the faces of helices α1 and α2 of FliS.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Helices α1 and α2 were oriented in a half-opened hairpin structure and interacted with helices α3 and α4 of FliS. Helix 3 was embedded in the flagellar binding pocket, which was consistent with other FliS-FliC structural models (Evdokimov et al, 2003;Altegoer et al, 2018;Xing et al, 2018). Helix 4 was located near the faces of helices α1 and α2 of FliS.…”
Section: Resultssupporting
confidence: 81%
“…The H. pylori flagellins FlaA and FlaB each contain four domains, consistent with other flagellin homologs (Beatson et al, 2006). Although the FliS-FliC structures have been resolved in A. aeolicus, B. subtilis and S. Typhimurium (Evdokimov et al, 2003;Altegoer et al, 2018;Xing et al, 2018), recent studies have demonstrated that the C-terminal D0 domain of flagellin is critical to the ability of H. pylori to evade TLR-5-mediated host recognition (Forstnerič et al, 2017). Therefore, the atomic details of FlaA/FlaB and the mechanism of binding to FliS are important.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations